The relationships between body weight, appetite, depression, and anxiety: Findings from the Texas Youth Depression and Suicide Research Network (TX-YDSRN) - Vadym Zhyrov; April Gorman; Rachel A Walker; Holli Slater; Emine Rabia Ayvaci; Shane A Snyder; Lynnel C Goodman; Emma Ableman; Abu Minhajuddin; Joshua S Elmore; Yasmin AlZubi; Kendall N Drummond; et al. (Health Psychology Open)
This study explored the association between body mass index (BMI), weight and appetite change, the severity of depression and anxiety, and related physical symptoms in youth seeking treatment for depression and/or suicidality. Youth completed self-report surveys and were categorized by BMI into healthy weight, overweight, and obese groups. Findings demonstrated overweight and obese participants were more likely to come from low-income households. Obese youth were more likely to report recent increases in appetite compared to healthy and overweight youth and in perceived weight compared to healthy weight youth. Obese youth had worse depression severity than overweight youth and worse physical function compared to healthy and overweight youth. Appetite and perceived weight changes were generally associated with worse clinical symptoms, with appetite more consistently associated with poorer presentations. These findings suggest high BMI, particularly within the obese range, is of concern for depressed youth, potentially putting them at risk for poorer clinical characteristics.